The adoption of system theory by Markus (1983) on user resistance determinants of ERP System in Malaysia / Ainsarah Mushtari Nasution and Amri Mohamad - Nasution, Ainsarah Mushtari; Mohamad, Amri (Universiti Teknologi MARA, Cawangan Melaka, 2019)
In nowadays, the use of technology for managing the information becomes crucial for most of the businesses. The phenomenon is complemented with the urge by the government for all enterprises to go digital in their day-to-day business processes. This has resulted in the increasing demand for information technology (IT) adoption, specifically the Enterprise Resource Planning (ERP) System. Consequently, the adoption has also led the increasing debate in relation to the issue of the system usage among the end-users, which is user resistance. The purpose of this paper is to provide the idea for revalidation of the factors for Malaysia employees to avoid from active use of ERP System by applying the System Theory.